2014
DOI: 10.1177/0004563214530676
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 17 α-hydroxyprogesterone in bloodspots by liquid chromatography tandem mass spectrometry

Abstract: Background: Monitoring of treatment for patients diagnosed with congenital adrenal hyperplasia (CAH) can be performed by measuring the concentration of 17a-hydroxyprogesterone (17OHP) in bloodspots collected on filter papers. A method is described here for measuring 17OHP by liquid chromatography tandem mass spectrometry (LCMSMS). Methods: 17OHP was extracted by liquid-liquid extraction and analysed by LCMSMS. The method was validated for sensitivity, specificity, linearity, recovery, ion suppression, precisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…LCMSMS removes interference from other steroids but can be prone to interference from other isobaric steroids, a number of which can be present in newborn bloodspots. 11-deoxycorticosterone, an aldosterone precursor, has previously been shown to interfere with 17OHP measurements by LCMSMS [9] when present in large quantities. Although concentrations are normally much lower than 17OHP and even absent in 21-hydroxylase deficiency, we did not note any interfering peaks in our method in any of our specimens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LCMSMS removes interference from other steroids but can be prone to interference from other isobaric steroids, a number of which can be present in newborn bloodspots. 11-deoxycorticosterone, an aldosterone precursor, has previously been shown to interfere with 17OHP measurements by LCMSMS [9] when present in large quantities. Although concentrations are normally much lower than 17OHP and even absent in 21-hydroxylase deficiency, we did not note any interfering peaks in our method in any of our specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Salter et al [ 9 ] and Janzen et al [ 10 ] found poor correlation between LCMSMS and radioimmunoassay in a small number of CAH patient samples. When comparing the two techniques, Boelen et al reported that LCMSMS measurements in neonatal samples were up to 75% lower than immunoassay [ 15 ], while Dhillon et al showed that the difference between LCMSMS and immunoassay was much wider in very low birth weight babies [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proven in newborn screening, however, that the use of LC/MS‐SIM has much higher accuracy in 17OHP determination . It can also be applicable in adults for the purposes of NCCAH diagnosis as shown by Salter et al . Lack of correlation between basal serum 17OHP level and urinary 17OHP metabolites in our study may speak for the hypothesis of the role of immunoassay reliability in the assessment of 17OHP.…”
Section: Discussionmentioning
confidence: 60%